The big change : America transforms itself, 1900-1950 - Allen, Frederick Lewis, 1890-1954 (New York : Harper & Brothers Publishers, 1952)
A survey of major changes in American life and ideas during the first half of the twentieth century, focusing on economic expansion and its influence on the American standard of living, thinking, and citizenship.
Keywords: National characteristics, American; United States -- Civilization -- 20th century; United States -- Economic conditions -- 1918-1945; United States -- Social conditions -- 1918-1932; United States -- Social conditions -- 1933-1945; United States -- Social conditions; United States -- Economic conditions